Department of Pre-University Education, KarnatakaPUC Karnataka Science Class 11

# P Find N in the Binomial ( 3 √ 2 + 1 3 √ 3 ) N , If the Ratio of 7th Term from the Beginning to the 7th Term from the End is 1 6 - Mathematics

Find n in the binomial $\left( \sqrt[3]{2} + \frac{1}{\sqrt[3]{3}} \right)^n$ , if the ratio of 7th term from the beginning to the 7th term from the end is  $\frac{1}{6}$

#### Solution

In the binomail expansion of  $\left( \sqrt[3]{2} + \frac{1}{\sqrt[3]{3}} \right)^n$ $\left[ \left( n + 1 \right) - 7 + 1 \right]^{th}$  i.e., (n − 5)th term from the beginning is the 7th term from the end.
Now,

$T_7 =^n C_6 \left( \sqrt[3]{2} \right)^{n - 6} \left( \frac{1}{\sqrt[3]{3}} \right)^6 =^n C_6 \times 2^\frac{n}{3} - 2 \times \frac{1}{3^2}$

$\text{ And, }$

$T_{n - 5} =^n C_{n - 6} \left( \sqrt[3]{2} \right)^6 \left( \frac{1}{\sqrt[3]{3}} \right)^{n - 6} =^n C_6 \times 2^2 \times \frac{1}{3^\frac{n}{3} - 2}$

It is given that,

$\frac{T_7}{T_{n - 5}} = \frac{1}{6}$

$\Rightarrow \frac{{}^n C_6 \times 2^\frac{n}{3} - 2 \times \frac{1}{3^2}}{{}^n C_6 \times 2^2 \times \frac{1}{3^\frac{n}{3} - 2}} = \frac{1}{6}$

$\Rightarrow 2^\frac{n}{3} - 2 - 2 \times 3^\frac{n}{3} - 2 - 2 = \frac{1}{6}$

$\Rightarrow \left( \frac{1}{6} \right)^{4 - \frac{n}{3}} = \frac{1}{6}$

$\Rightarrow 4 - \frac{n}{3} = 1$

$\Rightarrow n = 9$

Hence, the value of is 9.

Concept: Rth Term from End
Is there an error in this question or solution?

#### APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 18 Binomial Theorem
Exercise 18.2 | Q 38 | Page 40